Towards standardised biomonitoring of airborne microfibres by lichen transplants: Role of pre-cleaning, exposure time and weather - Zulema Varela; Anna Gaglione; María Bouso; Simonetta Giordano; J. Ángel Fernández; Fiore Capozzi; Valeria Spagnuolo (Environmental Research, 2026)

NeuraMFs: A deep learning model for airborne microfiber identification in plant biomonitors - Anna Gaglione; Sabato Fusco; Angelo Granata; Maria Cristina Sorrentino; Simonetta Giordano; Fiore Capozzi; Roberto Nardone; Valeria Spagnuolo (Journal of Hazardous Materials, 2026)

Effects of polystyrene microbeads on seed germination, plant growth and nutrient uptake in two landraces of Capsicum annuum L - Anna Gaglione; Angelo Granata; Maria Cristina Sorrentino; Luigi Rosati; Lorenzo Riccio; Simona Vingiani; Pasquale Ruocco; Simonetta Giordano; Valeria Spagnuolo; Fiore Capozzi (Environmental Research, 2026)

Different seed priming techniques variously modulate pre-germinative metabolism and germination performance in three Capsicum annuum cultivars - Angelo Granata; Maria Cristina Sorrentino; Simone Landi; Anna Gaglione; Sergio Esposito; Fiore Capozzi; Valeria Spagnuolo (Plant Biosystems, 2026)

Elemental profile and enological characteristics of Vitis vinifera L. cv. Aglianico grapes from a quality wine terroir in southern Italy: relationship with soil composition and chemical properties - Simona Vingiani; Fiore Capozzi; Angelita Gambuti; Pasquale Ruocco; Annina Caputo (Food Chemistry, 2025)

Microplastics, microfibers and associated microbiota biofilm analysis in seawater, a case study from the Vesuvian Coast, southern Italy - Manuela Rossi; Alessandro Vergara; Romualdo Troisi; Miriam Alberico; Federica Carraturo; Michela Salamone; Simonetta Giordano; Fiore Capozzi; Valeria Spagnuolo; Filippo Ambrosi de Magistris; Carlo Donadio; Viviana Scognamiglio; et al. (Journal of Hazardous Materials, 2025)

Sequential extraction of anthropogenic microfibers from the leaves of Pittosporum tobira - Fiore Capozzi; Angelo Granata; Anna Gaglione; Tina Gargiulo; Antonio Rallo; Francesca Marino; Maria Cristina Sorrentino; Concetta Pironti; Alessandro Vergara; Valeria Spagnuolo; Simonetta Giordano (Chemosphere, 2024)

A new green protocol for the identification of microplastics and microfibers in marine sediments, a case study from the Vesuvian Coast, Southern Italy - Manuela Rossi; Alessandro Vergara; Fiore Capozzi; Simonetta Giordano; Valeria Spagnuolo; Romualdo Troisi; Vincenzo Vedi; Filippo Ambrosi de Magistris; Noemi Fiaschini; Tonia Tommasi; Marco Guida; Mariarca D’Aniello; et al. (Journal of Hazardous Materials, 2024)

Light-responsive kinetic façade system inspired by the Gazania flower: A biomimetic approach in parametric design for daylighting - Francesco Sommese; Seyed Morteza Hosseini; Lidia Badarnah; Fiore Capozzi; Simonetta Giordano; Veronica Ambrogi; Gigliola Ausiello (Building and Environment, 2024)

Facing metal stress by multiple strategies: morphophysiological responses of cardoon (Cynara cardunculus L.) grown in hydroponics - Maria Cristina Sorrentino; Fiore Capozzi; Chiara Amitrano; Gaetano De Tommaso; Carmen Arena; Mauro Iuliano; Simonetta Giordano; Valeria Spagnuolo (Environmental Science and Pollution Research, 2021)
The contamination of environments by heavy metals has become an urgent issue causing undesirable accumulations and severe damages to agricultural crops, especially cadmium and lead which are among the most widespread and dangerous metal pollutants worldwide. The selection of proper species is a crucial step in many plant-based restoration approaches; therefore, the aim of the present work was to check for early morphophysiological responsive traits in three cultivars of Cynara cardunculus (Sardo, Siciliano, and Spagnolo), helping to select the best performing cultivar for phytoremediation. For all three tested cultivars, our results indicate that cardoon displays some morphophysiological traits to face Cd and Pb pollution, particularly at the root morphology level, element uptake ability, and photosynthetic pigment content. Other traits show instead a cultivar-specific behavior; in fact, stomata plasticity, photosynthetic pattern, and antioxidant power provide different responses, but only Spagnolo cv. achieves a successful strategy attaining a real resilience to metal stress. The capacity of Spagnolo plants to modify leaf structural and physiological traits under heavy metal contamination to maintain high photosynthetic efficiency should be considered an elective trait for its use in contaminated environments.

Exploring the phytoremediation potential of Cynara cardunculus: a trial on an industrial soil highly contaminated by heavy metals - Fiore Capozzi; Maria Cristina Sorrentino; Antonio Giandonato Caporale; Nunzio Fiorentino; Simonetta Giordano; Valeria Spagnuolo (Environmental Science and Pollution Research, 2020)

Background element content in the lichen Pseudevernia furfuracea: a comparative analysis of digestion methods - Elva Cecconi; Guido Incerti; Fiore Capozzi; Paola Adamo; Roberto Bargagli; Renato Benesperi; Fabio Candotto Carniel; Sergio Enrico Favero-Longo; Simonetta Giordano; Domenico Puntillo; Sonia Ravera; Valeria Spagnuolo; et al. (Environmental Monitoring and Assessment, 2019)

Overall plant responses to Cd and Pb metal stress in maize: Growth pattern, ultrastructure, and photosynthetic activity - Francesca Figlioli; Maria Cristina Sorrentino; Valeria Memoli; Carmen Arena; Giulia Maisto; Simonetta Giordano; Fiore Capozzi; Valeria Spagnuolo (Environmental Science and Pollution Research, 2019)

Infraspecific variability in baseline element composition of the epiphytic lichen Pseudevernia furfuracea in remote areas: implications for biomonitoring of air pollution - Guido Incerti; Elva Cecconi; Fiore Capozzi; Paola Adamo; Roberto Bargagli; Renato Benesperi; Fabio Candotto Carniel; Fabiana Cristofolini; Simonetta Giordano; Domenico Puntillo; Valeria Spagnuolo; Mauro Tretiach (Environmental Science and Pollution Research, 2017)